Report of the interactive workshop on lessons learnt and best practices for enhancing governance of African large Marine ecosystems - AU-IBAR (AU-IBAR, 2014)
Report of the interactive workshop on lessons learnt and best practices for enhancing governance of African large Marine ecosystems. Meeting was held from 17-19 December 2014 Douala, Cameroon.
Keywords: Marine Ecosystems; FishGov 1 Project